Suubi + Adherence4Youth: a study protocol to optimize the Suubi Intervention for Adherence to HIV treatment for youth living with HIV in Uganda - Fred M. Ssewamala; John A. Sauceda; Rachel Brathwaite; Torsten B. Neilands; Proscovia Nabunya; Derek Brown; Ozge Sensoy Bahar; Flavia Namuwonge; Noeline Nakasujja; Allan Mugarura; Abel Mwebembezi; Portia Nartey; et al. (BMC, 2023)
Abstract Background Suubi is an evidenced based multi-component intervention that targets psychosocial and economic hardships to improve ART adherence, viral suppression, mental health, family financial stability, and family cohesion for adolescents living with HIV (ALHIV) in Uganda. Suubi was originally tested as a combined package of four components: 1) Financial Literacy Training; 2) incentivized matched Youth Savings Accounts with income-generating activities; 3) a manualized and visual-based intervention for ART adherence and stigma reduction; and 4) engagement with HIV treatment-experienced role models. However, it is unknown if each component in Suubi had a positive effect, how the components interacted, or if fewer components could have produced equivalent effects. Hence, the overall goal of this new study is to identify the most impactful and sustainable economic and psychosocial components across 48 health clinics in Uganda. Methods A total of 576 ALHIV (aged 11-17 years at enrollment) will be recruited from 48 clinics and each clinic will be randomized to one of 16 study conditions. Each condition represents every possible combination of the 4 components noted above. Assessments will be conducted at baseline, 12, 24, 36 and 48- months post-intervention initiation. Using the multi-phase optimization strategy (MOST), we will identify the optimal combination of components and associated costs for viral suppression, as well as test key mediators and moderators of the component-viral suppression relationship. Discussion The study is a shift in the paradigm of research to use new thinking to build/un-pack highly efficacious interventions that lead to new scientific knowledge in terms of understanding what drives an intervention's success and how to iterate on them in ways that are more efficient, affordable and scalable. The study advances intervention science for HIV care outcomes globally. Trial Registration This project was registered at clinicaltrials.gov (NCT05600621) on October, 31, 2022. https://clinicaltrials.gov/ct2/show/NCT05600621